2020
DOI: 10.20411/pai.v5i1.374
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Temporary Loss of Taste and Olfactory Senses in SARS-CoV-2-positive-Individuals with Mild Symptoms

Abstract: SARS-CoV-2 infection has been characterized as an upper and lower respiratory tract infection with symptoms ranging from sore throat, cough, headache, and fatigue to a severe respiratory syndrome that requires intensive care [1-7]. Although a lower death rate has been recorded for SARS-CoV-2 in comparison to other recent coronavirus outbreaks, such as MERS or SARS, a compromised respiratory status on admission has been associated with fatal outcomes. Among the >1200 SARS-CoV-2-infected individuals in German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
5
11
0
3
Order By: Relevance
“…Schmithausen et al found that early temporary loss of taste and smell occurred in 68% of oligosymptomatic patients tested positive for SARS-CoV-2 after a cluster outbreak at a carnival celebration in North Rhine Westphalia, Germany, less than 100km away from our o ces (29). Similary to our study (80%), the most common symptom was a dry, non-productive cough (73%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Schmithausen et al found that early temporary loss of taste and smell occurred in 68% of oligosymptomatic patients tested positive for SARS-CoV-2 after a cluster outbreak at a carnival celebration in North Rhine Westphalia, Germany, less than 100km away from our o ces (29). Similary to our study (80%), the most common symptom was a dry, non-productive cough (73%).…”
Section: Discussionsupporting
confidence: 87%
“…A more focused approach of smear-taking has been used since the advent of clustered outbreaks (29) with a large amount of positives alongside a very low number of positives, such as in our area. The debate on the idealsmear strategy is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Schmithausen et al found that early temporary loss of taste and smell occurred in 68% of oligosymptomatic patients who tested positive for SARS-CoV-2 after a cluster outbreak at a carnival celebration in North Rhine-Westphalia, Germany, less than 100km away from our o ces (29). Similar to our study (80%), the most common symptom was a dry, non-productive cough (73%).…”
Section: Discussionsupporting
confidence: 85%
“…A more focused approach of smear-taking has been used since the advent of clustered outbreaks (29), with a large number of positive tests along with a very low number of positive tests, such as in our area. The debate on the ideal smear strategy is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a particularly complex pathogen because especially mild forms of the disease are often non-specific or asymptomatic, 2 and therefore, symptom-based risk management is not possible.…”
Section: Letter To the Editormentioning
confidence: 99%